Obstacle detection using a miniaturized radar sensor operating at 120GHz ISM band - Nava, Federico; Genschow, Dieter; Scheytt, Christoph (DRONE Berlin 2016)
Currently, all drone manufactures face the same problem: flight safety utility will become mandatory to obtain the legal admission for broad commercial use of drones. This means that on-board obstacle detection and collision avoidance is a must-have in order to overcome existing legal barriers and acceptance issues. Some of the currently available sensors are too large, too heavy, or can be poorly integrated into existing systems. During the exhibition a demonstration of a novel micro-sensor operating at 120 GHz will be given and participants will have the chance to experience the device first-hand.

Linear ultra-broadband NPN-only analog correlator at 33 Gbps in 130nm SiGe BiCMOS technology - Javed, Abdul Rehman; Scheytt, Christoph; Von der Ahe, Uwe (IEEE Bipolar/BiCMOS Circuits and Technology Meeting)
An ultra-broadband analog correlator consisting of a four-quadrant multiplier and an ultra-fast resettable integrator using only NPN transistors was designed, fabricated, and measured. For the integrator, a cross-coupled transistor pair is used as a negative resistance generator. A novel ultra-fast reset circuit is implemented which allows to reset the integrator within very short time of 120 ps. The chip was fabricated using 130 nm SiGe BiCMOS technology with fT of 250 GHz and f max of 300 GHz. In the measurements carried out on printed circuit board, the correlator operated without noticeable performance degradation with inputs up to 33 Gbps which correspond to a bandwidth of more than 24 GHz. The correlator exhibits high linearity with output P1dB of more than 9.9 dBm (700 mV diff ) for both inputs. It dissipates 122.5 mW for the core circuit excluding the 50 Ω output driver. To the knowledge of the authors, the circuit represents the fastest analog correlator published so far. It can be used for spread spectrum communication, radar signal processing, and measurement applications.

Hierarchical Scheduling for Plug-and-Produce - Jatzkowski, Jan; Adelt, Peer; Rettberg, Achim (3rd International Conference on System-integrated Intelligence: New Challenges for Product and Production Engineering)
Today's increasing number of sensors and computation nodes covered by cyber physical systems (CPS) results in rising complexity. For instance, computation results are based on measured data whose quality strongly depends on their age. CPS therefore have real-time requirements on computation results and communication to keep temporal dependency between measured inputs and computed outputs. In addition, today's CPS shall be modular to enable flexibility and scalability, e.g., postulated for production systems in context of Industry 4.0. Enabling CPS to easily integrate components by some Plug-and-Produce mechanism is desired.In this paper, we aim at enabling Plug-and-Produce in CPS using hypervisor-based virtualization. This implies hierarchical scheduling of dependent real-time systems. Here, dependencies are given by precedence constraints of tasks. Based on an approach for detection of new components added to a real-time network, in this paper we focus on integration of enabled applications into the current schedule of a computation node. Here, enabled application refers to an application software that just got executable by plugging some component to the CPS. Applications are encapsulated by virtual machines and provide a self-description including information about required and provided data as well as timing behavior. This self-description is used to adjust global scheduling and thus include new functionality to the CPS.

Ultra-compact 122GHz Radar Sensor for Autonomous Aircrafts - Nava, Federico; Scheytt, Christoph; Zwick, Thomas; Pauli, Mario; Goettel, B.; Winkler, Wolfgang (3rd International Conference on System-Integrated Intelligence)
In this paper a prototype of an ultra-compact continuous-wave (CW) and frequency-modulated continuous-wave (FMCW) radar system using a highly-integrated radar chip and in-package antennas will be presented. An introduction will be given on the concept of antenna integration for millimeter-wave radar and the advantages of such systems. The radar then will be described in its main components, a 122 GHz Integrated Circuit including in-package antennas as well as the acquisition and processing system realized using flexible printed circuit board (FLEX PCB) technology. Furthermore initial measurements of the radar system will be presented and explained.

Some reflections on electromagnetic force in matter - Böcker, Joachim (2016 International Symposium on Power Electronics, Electrical Drives, Automation and Motion (SPEEDAM))

Local demand response and load planning system for intelligent domestic appliances - Stille, Karl Stephan Christian; Böcker, Joachim (2015 International Conference on Renewable Energy Research and Applications (ICRERA))

Integration of home photovoltaic generation into electricity tariff for load optimization - Stille, Karl Stephan Christian; Böcker, Joachim; Fröhleke, Norbert; Bettentrup, Ralf; Kaiser, Ingo (2016 4th International Istanbul Smart Grid Congress and Fair (ICSG))

Local grid load coordination for load-shiftable domestic appliances in a variable-tariff environment - Stille, Karl Stephan Christian; Böcker, Joachim; Fröhleke, Norbert; Bettentrup, Ralf; Kaiser, Ingo (2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe))

Supervisional load optimization for households with intelligent domestic appliances - Stille, Karl Stephan Christian; Böcker, Joachim; Fröhleke, Norbert; Bettentrup, Ralf; Kaiser, Ingo (2016 10th International Conference on Compatibility, Power Electronics and Power Engineering (CPE-POWERENG))

A Critical Review of Techniques to Determine the Magnet Temperature of Permanent Magnet Synchronous Motors under Real-time Conditions - Wallscheid, Oliver; Huber, Tobias; Peters, Wilhelm; Böcker, Joachim (EPE Journal)

Real-time capable model predictive control of permanent magnet synchronous motors using particle swarm optimisation - Wallscheid, Oliver; Ammann, Ulrich; Böcker, Joachim (PCIM Europe 2016; International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)

2D analytical model for estimation of eddy current loss in the magnets of IPM machines considering the reaction field of the induced eddy currents - Paradkar, Milind; Böcker, Joachim (2015 IEEE International Electric Machines & Drives Conference (IEMDC))

Voltage controller for flux weakening operation of interior permanent magnet synchronous motor in automotive traction applications - Huber, Tobias; Peters, Wilhelm; Böcker, Joachim (2015 IEEE International Electric Machines & Drives Conference (IEMDC))

Analysis of eddy current losses in the stator windings of IPM machines in electric and hybrid electric vehicle applications - Paradkar, M.; Böcker, Joachim (8th IET International Conference on Power Electronics, Machines and Drives (PEMD 2016))

Comparison of quarter-wave with half-wave symmetrical pulse patterns applied in electrical high-speed drives - Peter, K.; Böcker, Joachim; Mink, F.; Beineke, S. (8th IET International Conference on Power Electronics, Machines and Drives (PEMD 2016))

Comparison of Optimized Pulse Patterns with Direct Model Predictive Control Using Co-Simulation - Schulte, C.; Peter, K.; Böcker, Joachim; Leuer, M. (8th IET International Conference on Power Electronics, Machines and Drives (PEMD 2016))

Inverter loss management for an electrical high-speed drive system - Peter, Klaus; Hanke, Soren; Mink, Fabian; Böcker, Joachim (2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe))

Sensitivity analysis on production tolerances for electric drive systems in automotive application - Ott, Markus; Böcker, Joachim (2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe))

Model predictive control strategy for multi-phase thyristor matrix converters — Advantages, problems and solutions - Leuer, Michael; Lönneker, Michael; Böcker, Joachim (2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe))

Comparison of the performance of gallium nitride (GaN) transistors in a totem-pole power factor controlled (PFC) rectifier - Bolte, Sven; Fröhleke, Norbert; Böcker, Joachim (2016 IEEE International Telecommunications Energy Conference (INTELEC))